2021
DOI: 10.1093/eurheartj/ehab431
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 deficiency rewires heart metabolism and drives heart failure with preserved ejection fraction

Abstract: Aims PCSK9 is secreted into the circulation, mainly by the liver, and interacts with low-density lipoprotein receptor (LDLR) homologous and non-homologous receptors, including CD36, thus favouring their intracellular degradation. As PCSK9 deficiency increases the expression of lipids and lipoprotein receptors, thus contributing to cellular lipid accumulation, we investigated whether this could affect heart metabolism and function. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 35 publications
4
54
1
1
Order By: Relevance
“…In our previous study, we demonstrated that adult ventricular cardiomyocytes constitutively express and secrete PCSK9 [ 12 , 26 ]. Moreover, secreted PCSK9 co-activates signal transduction pathways that depress cardiac function [ 14 , 26 ]. In line with these ex vivo studies, an inverse relationship between PCSK9 and cardiac function, quantified as left ventricular ejection fraction (LVEF), was shown [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated that adult ventricular cardiomyocytes constitutively express and secrete PCSK9 [ 12 , 26 ]. Moreover, secreted PCSK9 co-activates signal transduction pathways that depress cardiac function [ 14 , 26 ]. In line with these ex vivo studies, an inverse relationship between PCSK9 and cardiac function, quantified as left ventricular ejection fraction (LVEF), was shown [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The signaling of oxLDL involves LOX-1 (lectine-like oxidized low-density lipoprotein receptor-1) and dynamin-related protein 1 (Drp1), with the latter increasing mitochondria-induced oxidative stress [ 13 ]. Furthermore, PCSK9 deficiency may support heart failure [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship found in the present study could also be dependent on factors that still need to be investigated, given the complex interaction between lipid metabolism, PCSK9 and the heart [ 19 ]. Indeed, a recently published study on PCSK9 knock-out mice found that PCSK9 deficiency could negatively affect cardiac lipid metabolism (increased left ventricular thickness and an increased cardiac accumulation of lipid droplets were associated with a reduced density of mitochondrial cristae leading to impaired oxidative phosphorylation and mitochondrial metabolism) in a LDLR-independent manner, contributing to the development of HF and secondarily to high NPs levels [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study in mice showed that PCSK9 deficiency contributes to the development of HF with preserved ejection fraction. 21 …”
Section: Discussionmentioning
confidence: 99%